2019
DOI: 10.1021/acs.analchem.9b02075
|View full text |Cite
|
Sign up to set email alerts
|

Probing the Fundamentals of Native Liquid Extraction Surface Analysis Mass Spectrometry of Proteins: Can Proteins Refold during Extraction?

Abstract: Native ambient mass spectrometry has the potential for simultaneous analysis of native protein structure and spatial distribution within thin tissue sections. Notwithstanding sensitivity, this information can, in principle, be obtained for any protein present with no requirement for a priori knowledge of protein identity. To date, native ambient mass spectrometry has primarily made use of the liquid extraction surface analysis (LESA) sampling technique. Here, we address a fundamental question: Are the protein … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
16
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(17 citation statements)
references
References 69 publications
(109 reference statements)
1
16
0
Order By: Relevance
“…34,35 However, refolding of holo-myoglobin was not observed in native LESA studies of surface dried sample, although adjusting native sampling solvent of 25mM ammonium acetate by 2.5% ammonium hydroxide led to ~ 3% of myoglobin detected as holo-protein. 33 Surprisingly, an extraordinary amount of refolding was observed during our native DESI studies of denatured myoglobin. As seen in Fig.…”
Section: Refolding Of Unfolded Proteins and Complexes In Native Desimentioning
confidence: 91%
See 2 more Smart Citations
“…34,35 However, refolding of holo-myoglobin was not observed in native LESA studies of surface dried sample, although adjusting native sampling solvent of 25mM ammonium acetate by 2.5% ammonium hydroxide led to ~ 3% of myoglobin detected as holo-protein. 33 Surprisingly, an extraordinary amount of refolding was observed during our native DESI studies of denatured myoglobin. As seen in Fig.…”
Section: Refolding Of Unfolded Proteins and Complexes In Native Desimentioning
confidence: 91%
“…Results presented in figures 3 and 4 showed that folded protein structures and intact protein complexes can be detected using DESI with a standard inlet capillary. In previous LESA studies, 29,33 structure collapse was observed during room temperature drying of droplets of proteins and protein complexes prepared in native conditions. Furthermore, refolding of unfolded proteins and protein complexes has been shown to occur when using native sampling solvent conditions for analysis of denatured samples.…”
Section: Refolding Of Unfolded Proteins and Complexes In Native Desimentioning
confidence: 99%
See 1 more Smart Citation
“…60,74,75 For example, TWIMS has been coupled to many ion sources including MALDI, 36,[76][77][78][79][80] DESI, 60,74,80,81 LAESI, 82,83 and LESA (Figure 2A-D). 48,61,84,85 is a point of much discussion in the scientific community. [85][86][87] In another example, Hale and colleagues showed that mobility information provided by TWIMS enabled filtering of spectral noise that contributed to improved ion image quality.…”
Section: Traveling Wave Ion Mobility Spectrometrymentioning
confidence: 99%
“…48,61,84,85 is a point of much discussion in the scientific community. [85][86][87] In another example, Hale and colleagues showed that mobility information provided by TWIMS enabled filtering of spectral noise that contributed to improved ion image quality. 61 For example, the authors…”
Section: Traveling Wave Ion Mobility Spectrometrymentioning
confidence: 99%